SUN-LB104 Metabolic Inflexibility: Is It a Feature of Obesity or a Characteristic of Metabolically Unhealthy Youth? - Gebara, Nour Y (J Endocr Soc, 2020)
Obese individuals have metabolic inflexibility evidenced by diminished fasting fat oxidation and blunted increase in respiratory quotient (RQ) from fasting to insulin-stimulated state. Metabolically unhealthy obese (MUHO) adolescents, unlike their metabolically healthy obese (MHO) peers, have unfavorable metabolic characteristics despite having comparable adiposity. We investigated if metabolic inflexibility is a characteristic of obesity per se or is unique to MUHO compared with MHO youth. Obese youth (n=188; age 14.1 ± 0.1 yrs [SE]; BMI 33.6 ± 0.4 kg/m(2)) were divided into 137 MUHO (age 14.1 ± 0.2 yrs; BMI 35.4 ± 0.5 kg/m(2)) and 51 MHO (age 13.9 ± 0.3 yrs; BMI 29.0 ± 0.7 kg/m(2)) based on cut points for in vivo insulin sensitivity (IS) [MHO within 1.5 SD and MUHO <1.5 SDs of 72 normal-weight (NW) adolescents’ IS values]. RQ (by indirect calorimetry) at fasting and during a hyperinsulinemic (80mu/m(2)/min)-euglycemic clamp was measured, and ∆RQ calculated. Body composition (by DEXA), visceral adipose tissue (VAT) (by CT and MRI), hepatic IS (HIS) (calculated from fasting hepatic glucose production by [6,6-(2)H(2)]glucose and fasting insulin), adipose IS (ATIS) (calculated from whole body lipolysis by [(2)H(5)]glycerol and fasting insulin), and peripheral IS were assessed. MUHO vs. MHO youth had blunted ∆RQ (0.088 ± 0.004 vs. 0.107 ± 0.007, p=0.035), but MHO was not different from NW (0.098 ± 0.004, p=0.893). Further, MUHO vs. MHO youth had lower HIS (15.3 ± 0.7 vs. 24.3 ± 1.6 (mg/kg/min·uU/mL)(-1), p<0.0001) and lower ATIS (9.8 ± 0.5 vs. 22.3 ± 3.1 (umol/kg/min·uU/mL)(-1), p<0.0001), but HIS and ATIS were not different between MHO and NW youth (24.3 ± 1.6 vs. 20.8 ± 1.2 (mg/kg/min·uU/mL)(-1), and 22.3 ± 3.1 vs. 22.0 ± 1.4 (umol/kg/min·uU/mL)(-1), p=ns for both). ∆RQ correlated with HIS (r=0.535), ATIS (r=0.288) and VAT (r=-0.309) (p<0.0001 for all), but not with BMI, BMI Z-scores or % body fat. The differences between MUHO and MHO youth in ∆RQ, HIS and ATIS remained significant after adjusting for % body fat, race, pubertal status and VAT. The present study reveals that metabolic inflexibility is not a feature of obesity, rather it is a characteristic of MUHO youth who have significantly lower ∆RQ compared with MHO youth, with no difference between MHO and NW youth. Moreover, MUHO compared with MHO youth have worse metabolic profile, represented in lower HIS and ATIS.